Pemberdayaan Komunitas Ibu CeTar (Cegah Stunting Anakku Cerdas) di Desa Mata Allo Kabupaten Gowa - Firawati Firawati; Hasma Hasma; Hasnaeni Hasnaeni (Lembaga Pengembangan Kinerja Dosen, 2025)
The Ibu Ce T Ar Community Empowerment Program (Prevent Stunting My Smart Child) in Mata Allo Village, Gowa Regency, aims to improve maternal health literacy and prevent stunting through a technology-based approach. Given the high rate of stunting (23%) associated with low maternal knowledge of exclusive breastfeeding and limited access to information, the program is designed in three stages: preparation and planning, training and dissemination, and promotion and socialization. In the initial stage, coordination with partners and the preparation of SOPs are carried out. Furthermore, cadres are intensively trained to use the Ce T Ar application, which is an educational and communication medium. The app comes with breastfeeding guidance features, discussion forums, online counseling support, and baby growth monitoring. The results of the evaluation showed a 32% increase in maternal knowledge after training, with the understanding of the importance of exclusive breastfeeding increasing from 45% to 90%. As many as 85% of participants actively use the app, which has been proven to help them implement correct breastfeeding practices. In terms of mentoring, 18 out of 20 mothers managed to provide exclusive breastfeeding for six months, while 15 mothers have implemented local MP-breastfeeding based on household food. The program also produces key cadre mentors who will train cadres in other villages, ensuring the sustainability of this initiative. Thus, this program shows great potential in empowering the community to prevent stunting in Mata Allo Village.